Effects of Aerobic and Resistance Exercise in Older Adults With Rheumatoid Arthritis: A Randomized Controlled Trial. Issue 1 (27th December 2018) - Lange, Elvira; Kucharski, Daniel; Svedlund, Sara; Svensson, Karin; Bertholds, Gunhild; Gjertsson, Inger; Mannerkorpi, Kaisa
Abstract : Objective: To evaluate the effect of a moderate‐to‐high–intensity, aerobic and resistance exercise with person‐centered guidance in older adults with rheumatoid arthritis (RA), through a randomized controlled multicenter trial. Methods: Older adults (ages 65–75 years) with RA (n = 74) were randomized to either a 20‐week exercise intervention at a gym (n = 36) or to home‐based exercise of light intensity (n = 38). Assessments were performed at baseline, at 20 weeks, and at 12 months. The primary outcome was the difference in the Health Assessment Questionnaire disability index (HAQ DI) score, and the secondary outcomes were the differences in physical fitness assessed by a cardiopulmonary exercise test, an endurance test, the timed up and go test, the sit to stand test, and an isometric elbow flexion force measurement. Results: No significant differences between the groups were found for the primary outcome, HAQ DI score. Within the intervention group there was a significant improvement in the HAQ DI score when compared to baseline ( P = 0.022). Aerobic capacity ( P < 0.001) and 3 of 4 additional performance‐based tests of endurance and strength significantly improved ( P < 0.05) in the intervention group when compared to the control group. In the intervention group, 71% of patients rated their health as much or very much improved compared to 24% of patients in the control group ( P < 0.001). At the 12‐month follow‐up, there were no significant differences in change between the 2 groups on the HAQ DI score. A significant between‐group difference was found for change in an endurance test ( P = 0.022). Conclusion: Aerobic and resistance exercise with person‐centered guidance improved physical fitness in terms of aerobic capacity, endurance, and strength in older adults with RA.